2018
DOI: 10.1093/jmcb/mjy067
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas WDR92 in association with R2TP-like complex and multiple DNAAFs to regulate ciliary dynein preassembly

Abstract: The motility of cilia or eukaryotic flagella is powered by the axonemal dyneins, which are preassembled in the cytoplasm by proteins termed dynein arm assembly factors (DNAAFs) before being transported to and assembled on the ciliary axoneme. Here, we characterize the function of WDR92 in Chlamydomonas. Loss of WDR92, a cytoplasmic protein, in a mutant wdr92 generated by DNA insertional mutagenesis resulted in aflagellate cells or cells with stumpy or short flagella, disappearance of axonemal dynein arms, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 60 publications
(118 reference statements)
3
41
2
Order By: Relevance
“…The phenotypic changes were caused by the reduction in the number of IDAs b and c, while IDAs f/I1 and g were almost unaffected or only slightly reduced, similarly to ODAs [51]. The biochemical studies revealed that MOT48 interacts with RuvBL1, RuvBL2, RPAP3, and DNAAF4/DYX1C (Table 1) [53].…”
Section: R2tp Complexes In the Dynein Arm Assemblymentioning
confidence: 97%
See 3 more Smart Citations
“…The phenotypic changes were caused by the reduction in the number of IDAs b and c, while IDAs f/I1 and g were almost unaffected or only slightly reduced, similarly to ODAs [51]. The biochemical studies revealed that MOT48 interacts with RuvBL1, RuvBL2, RPAP3, and DNAAF4/DYX1C (Table 1) [53].…”
Section: R2tp Complexes In the Dynein Arm Assemblymentioning
confidence: 97%
“…To date, mutations in RuvBL1 or RuvBL2 have not been associated with PCD in humans, likely because these proteins function as co-chaperones for the assembly of diverse protein complexes and their mutations would cause death during early development, as was observed in mice [15]. [53] IDA c,d,g [52] DNAH5, DNAI1, [34] DNALI1 [34] DNAAF7 DNAH5, DNAI2 [58] TCTEX1D1 [58] DNAH5 [35] DNAL1 [35] LRRC6 DNAI1, DNAI2 [37,38] DNAH7 DNALI2 [37,38] Similarly, the analyses of Chlamydomonas and Danio rerio mutants suggested the involvement of PIH1D1 in dynein arms' assembly. Comparative studies of Danio rerio WT and pih1d1_null mutant revealed the abnormal motility of sperm flagella and Kupffer's vesicle cilia caused by the loss of outer and inner dynein arms.…”
Section: R2tp Complexes In the Dynein Arm Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the data concerning interactions between DNAAFs, DNAAFs and dynein arms subunits, as well as DNAAFs and heat shock protein chaperones, are fragmentary. It is proposed that DNAAFs assist heat-shock protein chaperones in the folding and pre-assembly of these complexes [150,151].…”
Section: Factors Involved In Dynein Arms Preassemblymentioning
confidence: 99%